REORIENTING OURSELVES IN (BERGSONIAN) FREEDOM, FRIENDSHIP AND FEMINISM. Issue 1 (3rd March 2020) - Anderson, Pamela Sue; Bunnin, Nicholas
Abstract: Pamela Sue Anderson urges feminist philosophers to embrace Michèle Le Doeuff's revaluation of women in philosophy through according "fair value" to intuition as an intellectual faculty, a view of intuition articulated by Henri Bergson. She asks whether women who follow Bergson could be given fair value along with intuition. She turns from Le Doeuff's writings on intuition to writings by Bergson and by Beauvoir, but periodically returns to Le Doeuff herself. In the end, a picture of freedom, friendship and feminism emerges from readings of all three. This is a portrait of confident and capable interactions in creativity and dynamic projects, which transform our becoming within life, on the assumption that the love of friendship is between like-minded, embodied and interrelated selves. She explores whether we transform our lives in freedom and in love between friends. Although attracted to the human – and humane – solidarity in freedom of "great souls, " as in Beauvoir's women of action, she instead aligns herself with Le Doeuff's critical caution against naturalizing a timelessly abstract female soul for contemporary feminist philosophers. She concludes her proposed orientation with a Le Doeuffian feminist image of living life freely for and with friends.